Democracia em disputa?: as concepções de parlamentares do PT e PL durante a CPMI do 8 de Janeiro - Francisco, Rafaela Cisi (Universidade Federal de São Carlos, 2025)
This research aims to investigate how members of the Workers’ Party (PT) and the Liberal Party (PL) mobilized conceptions about democracy during the CPMI of January 8, in light of minimalist (Schumpeter, Przeworski), liberal (Berlin, Mill) and pluralist (Dahl, Mouffe) theories. The research performs a content analysis of the 23 minutes of the committee meetings, using the MAXQDA software to categorize speeches into three axes: characterization of the act, profile of the participants and democratic conceptions. The results show a narrative polarization. PT members defined the events as “antidemocratic” (98.9% of the speeches about the “Fato”) and the participants as “coup plotters” (83.5%), aligning themselves with the liberal perspective (37.3% of the mentions) when defending the democratic rule of law and institutional defense. On the other hand, the members of the PL downplayed the acts, describing them as “legitimate demonstrations” (43.7%) or characterizing them vaguely, without giving them greater meaning (52.4%), criticizing asymmetries in the justice system, and arguing that the current political regime in Brazil is undemocratic (66.1%). The analysis shows that both party members redefined the concept of democracy to legitimize political agendas: the PT congressmen who were part of the committee linked democracy to the rule of law (37.3% of liberal mentions), while the PL congressmen who were part of the committee constructed a narrative of “relative democracy,” questioning the impartiality of the system
Democracy in dispute?: the conceptions of PT and PL parliamentarians during the CPMI of January 8th
Keywords: Democracia; Análise de conteúdo; CPMI do 8 de Janeiro; Discurso político; Polarização; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO